Supporting Factors of Sex Workers Behavior on HIV/AIDS Prevention: A Qualitative Study - Nurul Fadlila; Hanifatur Rosyidah; Is Susiloningtyas (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
As of November 2018, the number of HIV cases in Semarang reached up to 546. Sex workers have the highest risk to contract HIV/AIDS due to many sexual couples exposure. In 2018, the number of HIV in Argorejo location has increased three times compared to 2017. The purpose of the study was to describe the source of female sex workers information media to act in an effort to prevent HIV / AIDS in the Argorejo Localization in Semarang City. This study used descriptive qualitative method. Data collection techniques was in-depth interviews. Population in this research is female sex workers in the Argorejo Localization, Semarang City. A descriptive phenomenological study was used describe the experience of female sex workers during in prostitution. Eleven female sex workers, a foster mother also two health workers as data resource triangulation to collect the data. This analysis also uses content analysis. Most of the sex workers have heard of HIV/AIDS from magazine, social media, sign or poster in dorm and from friends. HIV/AIDS cases that have occurred to the sex workers’ colleagues were one of the guides to behave or in other words considering the experience that has happened before is a strong predictor for behavior in the future.